PENGARUH PENAMBAHAN MODIFIER ASPAL YANG MENGANDUNG MANGAN (Mn) TERHADAP SIFAT REOLOGI DAN KARAKTERISTIK CAMPURAN - Tjitjik Wasiah Suroso (Direktorat Bina Teknik Jalan dan Jembatan, 2007)
The solution to cases of road pavement failure in accommodating traffic loads and densed traffic is needed. One of materials needed to increase the quality of road pavement is that the addition of additive containing Manganese component. The article describes the laboratory and field research result and the influence of the addition of additives containing manganese component on asphalt Rheological properties and asphalt mix performance both in the laboratory and field. The result showed that at early stage, the addition of additive decreased asphalt penetration value and decreased Marshall stability of asphalt mixture. Rheological properties and performance increased over time. Field experiment experiment conducted by Daniels (1990) cs showed that asphalt mix performance using additive containing manganese compound increased during service, and decreased layer thickness ranging between 20 to 30%. In another location film thickness increased about 30 – 45 % than conventional asphalt, and appeared crocodile cracks on the location with modifier, therefore experiment in different location should be conducted to gain effective result of the material. It is suggested that the materialis used in stable pavements when additive is used, the process and the influence of it on asphalt mixture should be studied. Key word : Modifier, Asphalt, Asphalt mixture, stability